Analyse von Skalierungseffekten beim Expansionsspritzgießen von Mikro- und Dünnwandbauteilen - Drummer, Dietmar; Vetter, Karoline (Kolloquium Mikroproduktion und Abschlusskolloquium SFB 499, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.analys

Analysis and Comparative Assessment of Different Process Technologies for Manufacturing Polymer Micro-Elements - Drummer, Dietmar; Hopmann, Christian; Vetter, Karoline; Meister, Steve; Fischer, Torben; Piotter, Volker; Prokop, Jürgen; Ehrenstein, Gottfried (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.analys

Die Forschergruppe 702: Maschinen-, Werkzeug- und Prozessentwicklung für neue Verfahren zur Herstellung von Mikrobauteilen über flüssige Phasen - Möhwald, Kai; Bach, Friedrich-Wilhelm; Drummer, Dietmar; Hopmann, Christian; Piotter, Volker; Fischer, Torben; Meister, Steve; Prehm, Jens; Prokop, Jürgen; Vetter, Karoline (Kolloquium Mikroproduktion und Abschlusskolloquium SFB 499, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.diefor

Early signs of architectural and biomechanical failure in isolated myofibers and immortalized myoblasts from desmin-mutant knock-in mice - Diermeier, Stefanie; Iberl, Julian; Vetter, Karoline; Haug, Michael; Pollmann, Charlotte; Reischl, Barbara; Buttgereit, Andreas; Schürmann, Sebastian; Spörrer, Marina; Goldmann, Wolfgang; Fabry, Ben; Elhamine, Fatiha; et al. (Scientific Reports, 2017)
In striated muscle, desmin intermediate filaments interlink the contractile myofibrillar apparatus with mitochondria, nuclei, and the sarcolemma. The desmin network's pivotal role in myocytes is evident since mutations in the human desmin gene cause severe myopathies and cardiomyopathies. Here, we investigated skeletal muscle pathology in myofibers and myofibrils isolated from young hetero- and homozygous R349P desmin knock-in mice, which carry the orthologue of the most frequent human desmin missense mutation R350P. We demonstrate that mutant desmin alters myofibrillar cytoarchitecture, markedly disrupts the lateral sarcomere lattice and distorts myofibrillar angular axial orientation. Biomechanical assessment revealed a high predisposition to stretch-induced damage in fiber bundles of R349P mice. Notably, Ca(2)(+)-sensitivity and passive myofibrillar tension were decreased in heterozygous fiber bundles, but increased in homozygous fiber bundles compared to wildtype mice. In a parallel approach, we generated and subsequently subjected immortalized heterozygous R349P desmin knock-in myoblasts to magnetic tweezer experiments that revealed a significantly increased sarcolemmal lateral stiffness. Our data suggest that mutated desmin already markedly impedes myocyte structure and function at pre-symptomatic stages of myofibrillar myopathies.
EVALuna2:7360

Einfluss der Prozesscharakteristik des Expansionsspritzgießens auf die Eigenschaften von Mikrobauteilen aus PP - Vetter, Karoline; Kühnert, Ines; Hülder, Gerrit; Drummer, Dietmar (Technomer, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.FT.FT-KT.einflu

Expansion-injection-molding (EIM) by cavity near melt compression - About the process characteristic - Drummer, Dietmar; Vetter, Karoline (CIRP Journal of Manufacturing Science and Technology, 2011)
To mold thin-walled and micro scaled parts high flow rates and injection speeds are required. Otherwise, incomplete filling can occur due to rapid cooling of the polymer. Furthermore, high flow rates improve the molding quality of microstructures. It is well known, that high injection speeds in micro-molding can cause a melt compression. Thus, the implied flow rates are not achieved and the process becomes unstable. Expansion-injection-molding (EIM) makes use of this physical effect of melt compressibility. In a first step of the process the melt is pressurized. Due to the pressure drop after opening the compression chamber a high flow rate develops. The filling process itself is not influenced by the machine-setup or process control. This paper introduces a new modular mold design for EIM by cavity near melt compression. The great advantage for micro-molding is the reduction of the length of the flow path and consequently of the pressure loss as well as the melt volume required. The process characteristic was analyzed by molding a downscaled tensile bar using a Polyoxymethylene resin. A robust process at very high flow rates was verified. In comparison to conventional injection molding the maximum flow rates were about 10 times higher. © 2011 CIRP.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KT.expans
Keywords: EIM; Expansion-injection-molding; High speed injection molding; Melt compression; Micro injection molding; Thin-wall injection molding

Influence of Expansion Injection Moulding (EIM) upon Part Properties - Drummer, Dietmar; Vetter, Karoline (44th Conference on Manufacturing Systems, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KT.influe

Innovative process technologies for manufacturing thermoplastic micro parts - Analysis and comparative assessment - Drummer, Dietmar; Hopmann, Christian; Vetter, Karoline; Meister, Steve; Fischer, Torben; Piotter, Volker; Prokop, Jürgen; Ehrenstein, Gottfried (Zeitschrift Kunststofftechnik, 2012)
Keywords: Expansion-injection-moulding; Mechanical properties; Micro injection moulding; Morphology; Mould material; Ultrasound

Innovative Prozesstechnologien für die Herstellung thermoplastischer Mikrobauteile - Analyse und vergleichende Bewertung - Drummer, Dietmar; Hopmann, Christian; Vetter, Karoline; Meister, Steve; Fischer, Torben; Piotter, Volker; Prokop, Jürgen; Ehrenstein, Gottfried (Zeitschrift Kunststofftechnik, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.innova

Measurement of mechanical material properties for micro parts on injection moulded micro tensile bars - Meister, Steve; Vetter, Karoline; Drummer, Dietmar; Ehrenstein, Gottfried (Zeitschrift Kunststofftechnik, 2013)
Keywords: Mechanical testing; Micro injection moulding; Moisture; Thermoplastics; Useful properties

Mechanische Kennwertermittlung für Mikrobauteile an spritzgegossenen Mikro-Zugprüfkörpern - Meister, Steve; Vetter, Karoline; Drummer, Dietmar (Zeitschrift Kunststofftechnik, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KT.mechan

Neue Prozesstechnologien für die Mikrofertigung - Drummer, Dietmar; Bach, Friedrich-Wilhelm; Hopmann, Christian; Möhwald, Kai; Piotter, Volker; Fischer, Torben; Meister, Steve; Prehm, Jens; Prokop, Jürgen; Vetter, Karoline; Ehrenstein, Gottfried (Mikroproduktion, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KT.neuepr

Spritzgießen von Mikrobauteilen durch Schmelzevorkompression - Drummer, Dietmar; Vetter, Karoline; Ehrenstein, Gottfried (3. Industriekolloquium der Forschergruppe 702, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.spritz

The MyoRobot technology discloses a premature biomechanical decay of skeletal muscle fiber bundles derived from R349P desminopathy mice - Haug, Michael; Meyer, Charlotte; Reischl, Barbara; Prölß, Gerhard; Vetter, Karoline; Iberl, Julian; Nübler, Stefanie; Schürmann, Sebastian; Rupitsch, Stefan; Heckel, Michael; Pöschel, Thorsten; Winter, Lilli; et al. (Scientific Reports, 2019)
Mutations in the Des gene coding for the muscle-specific intermediate filament protein desmin lead to myopathies and cardiomyopathies. We previously generated a R349P desmin knock-in mouse strain as a patient-mimicking model for the corresponding most frequent human desmin mutation R350P. Since nothing is known about the age-dependent changes in the biomechanics of affected muscles, we investigated the passive and active biomechanics of small fiber bundles from young (17–23 wks), adult (25–45 wks) and aged (>60 wks) heterozygous and homozygous R349P desmin knock-in mice in comparison to wild-type littermates. We used a novel automated biomechatronics platform, the MyoRobot, to perform coherent quantitative recordings of passive (resting length-tension curves, visco-elasticity) and active (caffeine-induced force transients, pCa-force, ‘slack-tests’) parameters to determine age-dependent effects of the R349P desmin mutation in slow-twitch soleus and fast-twitch extensor digitorum longus small fiber bundles. We demonstrate that active force properties are not affected by this mutation while passive steady-state elasticity is vastly altered in R349P desmin fiber bundles compatible with a pre-aged phenotype exhibiting stiffer muscle preparations. Visco-elasticity on the other hand, was not altered. Our study represents the first systematic age-related characterization of small muscle fiber bundle preparation biomechanics in conjunction with inherited desminopathy.
CRIS-Team Scopus Importer:2019-08-02